Review of convection heat transfer and fluid flow in porous media with nanofluid - Mahdi, Raed Abed (Elsevier Limited, 2015)
There are two advantages of using porous media. First, its dissipation area is greater than the conventional fins that enhances the heat convection. Second is the irregular motion of the fluid flow around the individual beads which mixes the fluid more effectively. Nanofluids result from the mixtures of base fluid with nanoparticles having dimensions of (1-100) nm, with very high thermal conductivities; as a result, it would be the best convection heat transfer by using two applications together: porous media and nanofluids. This article aims to summarize the published articles in respect to porosity, permeability (K) and inertia coefficient (Cf) and effective thermal conductivity (keff) for porous media, also on the thermophysical properties of nanofluid and the studies on convection heat transfer in porous media with nanofluid.